Current trends in silvopastoral systems - Peri, Pablo Luis; Chará, Julián; Viñoles, Carolina; Bussoni, Adriana; Cubbage, Frederick (Springer Nature, 2024)
In Latin America, SPS are practiced in various ecosystems in humid and dry broadleaved forests, temperate forests, tropical and subtropical coniferous forests, and savannas. These ecosystems range from sea level up to> 2000 m of altitude, from 5.6 to 28.4 °C mean annual temperature, and from 200 to 3500 mm yr−1 mean annual precipitation, and from 10 to 250 ha (Peri et al. 2019). The range of conditions in this region provides insights about how factors such as geography, climate, culture, and markets affect SPS selection and implementation. This special issue presents a current state of the art compendium about outcomes of SPS in Latin America based on manuscripts presented in the XII International Congress of Silvopastoral Systems held in Uruguay during October 2023. It is a transdisciplinary issue with papers covering the region’s biophysical, productive, social, and cultural aspects of SPS.